Beyond Public Scrutiny Stocktaking of Social Accountability in OECD Countries - Organisation for Economic Co-operation and Development; OECD eBooks; The World Bank. (Washington, D.C. : The World Bank, 2007)
This joint OECD-World Bank stocktaking exercise of social accountability (SA) initiatives in OECD member countries contributes to the global exchange of policy relevant knowledge. The stocktaking exercise produced 40 templates detailing social accountability initiatives in 27 OECD countries and the European Commission. Cases were selected on the basis of their focus and level, and potential transferability of their policy lessons.
Keywords: Governance; Electronic books